Development of a national neonatal intensive care unit-specific antimicrobial stewardship programme in Canada: protocol for a cohort study. Issue 12 (10th December 2020) - Ting, Joseph Y.; Roberts, Ashley; Tilley, Peter; Robinson, Joan L; Dunn, Michael S; Paquette, Vanessa; Lee, Kyong-Soon; Shah, Vibhuti; Yoon, Eugene; Richter, Lindsay L; Lodha, Abhay; Shivananda, Sandesh; et al.
Abstract : Introduction: Early empiric treatment with broad-spectrum antimicrobials is common in neonatal intensive care units (NICU) due to the non-specific clinical presentation of infection. However, excessive and inappropriate antimicrobial use can lead to the emergence of drug-resistant organisms and adverse neonatal outcomes. This study aims to develop and implement a nationwide NICU-specific antimicrobial stewardship programme (ASP) to promote judicious antimicrobial use and control the emergence of multidrug-resistant organisms (MDROs) in Canada. Methods and analysis: Our study population will include all very low-birth-weight neonates admitted to participating tertiary NICU in Canada. Based on the existing limited literature, we will develop consensus on NICU antimicrobial stewardship interventions to enhance best practices. Using an expanded Canadian Neonatal Network (CNN) platform, we will collect data on antimicrobial use and the susceptibility of organisms identified in clinical samples from blood and cerebrospinal fluid over a period of 2 years. These data will be used to provide all NICU stakeholders with benchmarked centre-adjusted antimicrobial use and MDRO prevalence reports. An ASP plan will be developed at both individual unit and national levels in the subsequent years. Knowledge translation strategies will be implemented through the well-established Evidence-based Practice for Improving Quality methodology. Ethics and dissemination: Ethics for the study has been granted by the University of British Columbia Children's & Women's Research Ethics Board (H19-02490) and supported by CNN Executive Committee. The study results will be disseminated through national organisations and open access peer-reviewed publications. Trial registration number: NCT04388293 .